Can extended curriculum programmes be improved through engagement with students using appreciative inquiry? - Ogude, N.A.; Meyer, I.J.; Mwambakana, J.; Mthethwa, N.E. (South African Journal of Higher Education, 2019)
This research involves eight students at the university under study [1] who identify with the BSc Extended Programmes. The study reports on the use of Appreciative Inquiry to determine how these students describe the best aspects of the programmes and the attributes that they developed to overcome the stigma and isolation associated with the programmes. The aim was to extrapolate the findings to develop an improvement plan informed by students’ perspectives. The narratives from semi‑structured interviews conducted during the Discovery and Dream stages of the modified Appreciative Inquiry 4‑D process are reported. Six views emerged: sense of family and belonging; peer mentoring and support networks; coping with failure and self-efficacy; the underdog phenomenon, self‑motivation and support for mainstream students; the student advising model; and extended curricular programmes as a first option. The attributes that students acquired to overcome stigmatisation and isolation are discussed. Further investigation of the six themes in the Design and Destiny phases is proposed to provide ideas that can engender resilience in more students.